Pembekalan Materi Akuntansi Keuangan Desa Pada Guru-Guru Akuntansi Sekolah Menengah Kejuruan - Novriansa, Agil; Wahyudi, Tertiarto; Aryanto (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2021)
The existence of an accounting practicum subject for government institutions/agencies in changing the curriculum structure of the Vocational High School in 2018 is a challenge for vocational accounting teachers in Palembang. One of the main topics in this subject is the preparation of village financial reports as a part of village financial accounting material.This community service activity aims to provide material for village financial accounting to vocational school accounting teachers in Palembang. This activity is carried out in the form of an online webinar via Zoom Meeting. This community service is a training in the form of education using lectures, tutorials and discussions. The form of evaluation that was carried out was that the participants were given a post-test to measure their understanding of village financial accounting material. The number of participants who participated in this community service activity was 34 vocational school accounting teachers in Palembang. This community service activity was carried out on November 14, 2020 starting from 09.30 until finished. There are 6 topics discussed in the provision of village financial accounting material, namely aspects of village finance law, village financial management, basic accounting concepts, accounting cycle stages, writing accounting evidence and preparing village financial reports. The results of the evaluation of community service activities are quite good and it can be concluded that the provision of village financial accounting material for vocational accounting teachers in Palembang is quite effective in providing advanced understanding of village financial accounting material.